Flavonoids and Naphthoflavonoids: Wider Roles in the Modulation of Cytochrome P450 Family 1 Enzymes. (23rd August 2016) - Dong, Jinyun; Zhang, Qijing; Cui, Qing; Huang, Guang; Pan, Xiaoyan; Li, Shaoshun
Abstract: The human cytochrome P450 family 1 enzymes consist of three members, CYP1A1, CYP1A2 and CYP1B1, which are predominantly involved in the phase I metabolism of xenobiotics. Because they have been implicated in carcinogenesis, cancer progression, and drug resistance, the inhibition of these enzymes has been widely considered an effective oncological therapeutic strategy. Some natural and synthetic flavonoids and naphthoflavonoids have been extensively documented to exert pronounced influence in the modulation of CYP1s, including functioning as inhibitors, substrates, and aryl hydrocarbon receptor (AhR) ligands. However, the molecular determinants behind these effects are still unknown. This review summarizes the structural features responsible for the CYP1 inhibitory effects of the reported flavonoids and naphthoflavonoids. Additionally, a three‐dimensional quantitative structure–activity relationship (3D‐QSAR) study was performed to better understand the effect of their structural properties on biological activities. We hope this review provides a useful foundation for the rational design of potent and selective CYP1 isozyme inhibitors, thereby accelerating the drug discovery process. Abstract : Cytochrome P450 family 1 enzymes (CYP1s) are implicated in carcinogenesis and drug resistance. Some natural and synthetic flavonoids and naphthoflavonoids have been documented to exert pronounced effects in the modulation of CYP1s, including roles as inhibitors, substrates, and aryl hydrocarbon receptor (AhR) ligands. Understanding the relationship between CYP1s and the structures of these compounds will significantly aid efforts in anticancer drug discovery.